New Tire Usage Efficiency by Increasing Lifetime Tyre Size 11.00R20 in DT Coal Hauling units in the Mining area of PT. Antareja Mahada Makmur Site PT MIFA Bersaudara Period (2024) - Nanang S; Fiqh'ya S.W; Reka T.; Jekson S; Ruli N. (Journal of World Science, 2025)
Tires represent the third-largest operational cost after fuel and maintenance in mining operations and contribute significantly to environmental waste. At PT Mahada Makmur, particularly at the MIFA jobsite, the 11.00R20 bias tire installed on the AXOR2528-CH hauling unit was observed to have suboptimal performance. This unit plays a critical role in coal transportation from the crusher to the port or power plant and has been modified (upsized) to carry loads up to 30 tons, exceeding the original design capacity of 20 tons. The research problem centers on the rapid wear and reduced lifespan of the bias tires under increased load conditions. The objective of this study is to identify the dominant factors affecting tire performance and propose an effective strategy to extend tire life. Using a three-month field observation method, the study evaluated the tire’s operational conditions and categorized influencing variables into maintenance, mechanical, operational, and product factors. Results indicated that operational factors, such as overloading and improper driving behavior, were the main contributors to premature tire wear. As a strategic solution, the study recommends tire standardization in accordance with actual load capacity and eliminating operational inefficiencies. The implication of this research is the potential for reduced tire costs, improved operational safety, and minimized environmental impact through more sustainable tire management practices.